Determination of Urolithin A in Health Products by Ultra-High-Performance Liquid Chromatography - Yue E; Zhuang Wang; Jiahui Nie (Molecules)
This study establishes and validates a novel ultra-high-performance liquid chromatography (UHPLC) method for the determination of urolithin A content in health products, a bioactive compound with potential anti-aging properties. Given the lack of standardized analytical methods for urolithin A in health products, this research addresses a critical gap in quality control. The method employs a methanol–water mobile phase, optimized gradient elution, and a specialized UPLC column (ACQUITY UPLC CSH Fluoro Phenyl) to achieve high resolution and specificity in the separation of urolithin A from its impurities. A variety of diluents, extraction solvents, and extraction times were tested to maximize analyte recovery and stability, with pure methanol yielding the highest recovery rate (over 95%) in 30 min. The method was validated in terms of linearity, sensitivity, repeatability, specificity, and precision. The calibration curve for urolithin A exhibited excellent linearity (r2 = 0.9998) over a concentration range of 0.100–10.000 µg/mL. Detection and quantification limits were found to be 0.051 µg/mL and 0.103 µg/mL, respectively. Precision testing revealed an inter-operator RSD of 1.3%, and recovery rates for spiked samples consistently fell within the 98–102% range. The developed method was successfully applied to analyze the urolithin A content in a commercially available health product, demonstrating its practicality for routine quality control. However, this method may currently be affected by the excipient matrix. This research contributes to the establishment of robust, reliable, and high-sensitivity analytical methods for the bioactive compounds found in health products, with significant implications for regulatory compliance and consumer safety.